Increasing Returns and Spatial Unemployment Disparities - Jens Suedekum (Hamburg Institute of International Economics (HWWA), 2004)
Regional unemployment rates in the European Union (EU-15) reveal a core-periphery structure. Large ?core? regions in the middle of the continent have low unemployment rates, whereas excessive mass unemployment is predominantly found in the peripheral regions at the outside borders of EU-15. This geographical pattern of unemployment rates follows the pattern of GDP per capita. That is, the regions with low (high) unemployment rates on average have comparatively high (low) real income levels. In this paper we try to understand this stylised fact with the help of a theoretical model that builds on two strings in the literature: the recent trade and location theories (like the new economic geography) and the wage curve. Standard models of the new location theories deal with regional disparities in production and income, but they usually assume full employment and are thus ill-equipped to study spatial unemployment disparities. The wage curve-approach, which explicitly shows how disparities in real wages and unemployment rates are interrelated, can not endogenously explain the origin of these asymmetries. In this paper, we combine these previously unrelated strings and develop a unified theoretical framework. We show that a core-periphery in real wages is associated and magnified by regional unemployment disparities. This wage curve relation is stable over time with an increasing returns technology. That is, the wage curve does not vanish as workers move from the periphery to the core, but it is rather reinforced by migration. These theoretical predictions of our model are in line with the empirical evidence.
Keywords: F4; R1; J6; 330; Regional Unemployment; Economic Geography; Increasing Returns; Wage Curve; Migration; Labor Mobility; Regionale Arbeitslosigkeit; Regionale Disparität; Regionale Lohnstruktur; Effizienzlohn; Regionalökonomik; Skalenertrag; Theorie; EU-Staaten